PENGARUH CORPORATE RISK, LEVERAGE, DAN LIQUIDITY TERHADAP AGRESIVITAS PAJAK PADA PERUSAHAAN SUB SEKTOR KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2020 - SEMBIRING, YAN CHRISTIN BR; SIDABUTAR, PURNAMA PEBRUARI (Jurnal Riset Akuntansi & Keuangan, 2022)
This study aims to determine the effect of corporate risk, leverage, and liquidity on tax aggressiveness in chemical sub-sector companies listed on the Indonesia Stock Exchange in 2016-2020. The population in this study were 12 chemical sub-sector companies. The sampling technique was purposive sampling in accordance with predetermined criteria, in order to obtain 7 sample companies with a research period of 5 years, so that the total sample data was 35 data. From the results of the SPSS test, it is known that the coefficient of determination (R square) is 0.288. This means that corporate risk, leverage, and liquidity together affect tax aggressiveness, namely 28.8%. Based on the results of multiple linear regression analysis, it can be concluded that corporate risk has a negative and insignificant effect on tax aggressiveness in chemical sub-sector companies listed on the Indonesia Stock Exchange in 2016-2020. Leverage has a negative and significant effect on tax aggressiveness in chemical sub-sector companies listed on the Indonesia Stock Exchange in 2016-2020. Liquidity has a negative and significant effect on tax aggressiveness in chemical sub-sector companies listed on the Indonesia Stock Exchange in 2016-2020.